The short run impacts of quantitative easing in the U.S. on ASEAN stock market indexes - Tee, Joash Way Ern (2022)
This dissertation investigates the short impact of U.S. quantitative easing (QE) on the daily movements of the 6 ASEAN stock market indexes (Malaysia, Singapore, Thailand, Vietnam, Philippines and Indonesia). The timeline of the analysis starts from the year 2008 to 2021 to cover the 4 main QE programs during this time. The analysis has 2 main stages of research. The first stage involves splitting the QE programs into individual timelines for analysis while the second stage consists of identify the country-specific results of the test from the combined results. Both stages of research use Ordinary Least Square (OLS) regression and Vector Error Correction Modelling (VECM) analysis. A 3 channel of transmission research methodology based upon the studies of Gagnon et al (2010) and Krishnamurthy and Vissing-Jorgensen (2011) is conducted on all tests. The results find that QE has a significant impact on the movements of the ASEAN stock market indexes and most of the impacts come from the portfolio balance and signalling channels of transmission via the interest rate spread and VIX values. QE2 and QE3 are the exception to this rule, both having an influence also in the liquidity channels via 3-month Treasury bill rate movements. The individual country analysis reports that the developed ASEAN countries such as Singapore and Malaysia were overall more sensitive to the effects of QE. In most of the findings, both OLS regression and VECM analysis are complementary in their results.